2016
DOI: 10.5194/bg-13-841-2016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sedimentary alkalinity release on the water column CO<sub>2</sub> system in the North Sea

Abstract: Abstract. It has been previously proposed that alkalinity release from sediments can play an important role in the carbonate dynamics on continental shelves, lowering the pCO 2 of seawater and hence increasing the CO 2 uptake from the atmosphere. To test this hypothesis, sedimentary alkalinity generation was quantified within cohesive and permeable sediments across the North Sea during two cruises in September 2011 (basin-wide) and June 2012 (Dutch coastal zone). Benthic fluxes of oxygen (O 2 ), alkalinity (A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 107 publications
10
72
4
Order By: Relevance
“…Generally, benthic processes linked to early diagenesis of organic matter can be an important source of A T to the water column (Brenner et al, 2016). This corresponds to the findings by Gustafsson et al (2014b), who, in a model study, found that external sinks and sources of A T in the Baltic Sea are imbalanced and cannot reproduce the observed A T inventory and that an internal A T source must exist in the Baltic Sea.…”
Section: Remineralizationsupporting
confidence: 83%
See 2 more Smart Citations
“…Generally, benthic processes linked to early diagenesis of organic matter can be an important source of A T to the water column (Brenner et al, 2016). This corresponds to the findings by Gustafsson et al (2014b), who, in a model study, found that external sinks and sources of A T in the Baltic Sea are imbalanced and cannot reproduce the observed A T inventory and that an internal A T source must exist in the Baltic Sea.…”
Section: Remineralizationsupporting
confidence: 83%
“…According to Eq. (2) this increases the seawater A T and thus raises the pH during biomass production (Brewer and Goldman, 1976). This assimilation also decreases the pCO 2 and therefore reinforces the drop in pCO 2 by biomass production.…”
Section: Biomass Productionmentioning
confidence: 67%
See 1 more Smart Citation
“…Using the basin characteristics (Table 1), the A T increase in Ringkøbing Fjord from April to September corresponds to an average areal flux of approximately 7.5 mmol m À2 d À1 . In fact, measurements by Brenner et al (2016) at numerous sites in the Southern North Sea revealed sediment to water A T fluxes in a range 0-21-.4 mmol m À2 d À1 (mean: 6.6 mmol m À2 d À1 ). In a numerical experiment, including A T sources and sinks in both sediments and water column, Brenner et al (2016) calculated a net A T generation in the water column of 2.4 mmol m À2 d À1 .…”
Section: Total Alkalinity In Estuarine Environmentsmentioning
confidence: 99%
“…In fact, measurements by Brenner et al (2016) at numerous sites in the Southern North Sea revealed sediment to water A T fluxes in a range 0-21-.4 mmol m À2 d À1 (mean: 6.6 mmol m À2 d À1 ). In a numerical experiment, including A T sources and sinks in both sediments and water column, Brenner et al (2016) calculated a net A T generation in the water column of 2.4 mmol m À2 d À1 . They identified the main A T sources as pelagic primary production and benthic CaCO 3 dissolution, denitrification, and sulfate reduction.…”
Section: Total Alkalinity In Estuarine Environmentsmentioning
confidence: 99%